Searching for initial stage of massive star formation around the H II region G18.2–0.3. (May 2017) - Zhang, Chuan-Peng; Yuan, Jing-Hua; Xu, Jin-Long; Liu, Xiao-Lan; Yu, Nai-Ping; Li, Nan; He, Li-Ping; Zhang, Guo-Yin; Wang, Jun-Jie
Abstract: Sometimes, early star formation can be found in cold and dense molecular clouds, such as an infrared dark cloud. Considering that star formation often occurs in clusters, HII regions may be triggering a new generation of star formation, so we can search for the initial stage of massive star formation around HII regions. Based on the above, this work introduces one method to search for the initial stage of massive star formation around HII regions. Towards one section of the HII region G18.2–0.3, multiwavelength observations are carried out to investigate its physical properties. Through analysis, we find three potential initial stages of massive star formation, suggesting that it is feasible to use in searching for the initial stage of massive star formation around HII regions.